FAKTOR – FAKTOR YANG MEMPENGARUHI ANIMO MASYARAKATUNTUK MENJADI PESERTA JAMINAN PEMELIHARAANKESEHATAN MASYARAKAT - -, Rakhmayanto; -, Saryono; Riyanti, Eka (Jurnal Ilmiah Kesehatan Keperawatan, 2013)
JPKM – theCommunity Health – Care Insurance is a health care financing program have beenorganized by the Government of Purbalingga since 2010. Some factors affects thepublic interest to participate in the JPKM program. The purpose of the researchis to find out the most dominant factor affecting the public interest to be aparticipant of the JPKM program on the village of Kalitinggar kidul, Padamara,Purbalingga, Central Java in the year of 2010.          The analytic method with cross sectional approach was used as theresearch method. The simple random technique was used to take the samples of144 respondents. The chi square andthe logisticregressionwas used toanalyze the data. The result of the chisquare test showed that the χ2value of the knowledge factor = 0,211 (p=0646); the χ2  value of thefamily income = 3,928 (p=192); the factor of the work social interaction factor= 19,057 (p=0,000); the χ2value of the public attitude = 1,623 (p=0,203); the χ2 value of the quality factor to the service of thePublic Health Center =   7,467 (p=0,058);theχ2 value of the qualityfactor to the Regional General Hospital = 3,360 (p=0,329). So it is got from theresult of the JPKM program is the factors affecting the public interest to theparticipation of the JPKM program is the work social interaction factor.  The conclusionof this research was a  relationshipbetween the work social  interaction  factor and the public interest to beparticipants of the JPKM program on the village of Kalitinggar kidul. The mostdominant factor affecting the public interest to be participants of the JPKMprogram is the work social interaction as well. Keywords: JPKM, participants, public interest, the dominant factor